“Help save the endangered pacific northwest tree octopus from extinction”: are 7th year students susceptible to fake news? - Meyrer, Karin Paola (2021)
Our fast-paced society requires schoolchildren to be skilled with the ability to identify online fake information in order not to be misled or influenced by the media and be capable of making well informed decisions. With this context in mind, this action research of a qualitative nature was developed with two groups of 7th year elementary schoolchildren from a private bilingual school (Portuguese-English) in Rio Grande do Sul (BR), during the remote learning period in English as a second language classes (ESL). Based on the theme endangered animals, the study seeks to verify if it is possible to develop critical media literacy in second language classes (L2) through interventions that challenge students to reflect about how to identify and investigate fake information. The study also aims at analyzing if the strategies developed during the interventions are employed in the creation of collective websites and what is the role of multimodal resources in students' interpretation of the theme endangered animals. The literature review is based on Literacy Studies (STREET, 1984, 1995; HEATH, 1983), Digital Literacies (DUDENEY, HOCKLY AND PEGRUM, 2013; JENKINS, 2009), Multiliteracies (THE NEW LONDON GROUP, 1996), Critical Literacy (FREIRE, 1987; JANKS, 2013), Critical Literacy and L2 learning (JORDÃO; FOGAÇA, 2012); and Critical Media Literacy (KELLNER; SHARE, 2007, 2016; KERSCH; LESLEY, 2019). As for the methodology, firstly students analyze a hoax website, partly replicating the study of Loos, Ivan and Leu (2018); secondly, a series of activities was developed; and, finally, students created their own collective websites about endangered animal species. The activities intended to contextualize the theme, potentialize students' abilities to verify online information, and develop reading and writing skills in English. To analyze students' collective websites, the Transpositional Grammar for Multimodality Analysis Framework of Kalantzis and Cope (2021) was used. On the one hand, the initial results showed that students have major difficulties in checking the lack of veracity in the fake website. On the other hand, they have proficiently employed the learnings acquired throughout the interventions in the production of their collective websites, confirming the development of critical media literacy in L2. Finally, a framework for incorporating CML in L2 is proposed, with the purpose of helping L2 educators who are willing to develop criticality in their lessons.